Techno-economic analysis of commercial-scale bioethanol production from oil palm trunk and empty fruit bunch - Suwajittanont, Pattamaporn; Thongrak, Phokhin; Srinophakun, Thongchai R. (Agriculture and Natural Resources, 2022)
Importance of the work: Lignocellulosic ethanol production from oil palm trunk (OPT) and empty fruit bunch (EFB) is considered a promising approach because the materials are abundant and inexpensive. Objectives: To produce ethanol 99.0 wt% and 10,000 L/d from OPT and EFB and to evaluate the economic feasibility using techno-economic analysis. Materials & Methods: The Aspen Plus Software was used to simulate the bioethanol production model. The scheduling of the batch process was generated using Aspen Batch Process Developer. Process controllability of the purification section was studied using Aspen Plus Dynamics. For economic feasibility, a techno-economic analysis (TEA) was performed. Results: The results indicated that bioethanol production with pervaporation was profitable when blended and sold as gasohol E20. In total, 48,000 kg/d of OPT and EFB were required to achieve the target capacity. Furthermore, increasing the OPT ratio provided a higher economic benefit. The best economic results in terms of the net present value, the internal rate of return and the payback period were at an OPT-to-EFB ratio of 75:25. The implemented control system in Aspen Plus Dynamics proved that the controllers could handle disturbances and control process variables to the desired specifications. Main finding: Extractive distillation and pervaporation were successfully used for ethanol dehydration. The highest ethanol production rate was by feeding only EFB and using pervaporation as purification technology. TEA indicated that the total capital investment of bioethanol production using pervaporation was higher than for extractive distillation.